Anti-inflammatory and barrier repair mechanisms of active components in Daemonorops draco Bl. for UVB-induced skin damage - Xingyi Wu; Ying Zhang; Fan Yi; Zaijun Geng; Miaomiao Guo; Xiao Ling; Jun Li; Li Li (Scientific Reports)
Abstract Daemonorops draco Bl. extract and its active ingredients can remove blood stasis and promote muscle and wound healing and are widely used in skin health and other fields. Modern pharmacological studies have demonstrated that this extract exerts excellent anti-inflammatory effects beneficial for skin barrier repair. However, the mechanism of action and monomeric components of D. draco remain unclear. Seven active monomers (XJ-1 ~ XJ-7) were extracted and purified from D. draco. The successful construction of the HaCaT inflammation model was achieved through the detection of IL-1β and TNF-α expressions in UVB-irradiated HaCaT cells. Based on this cellular model, (2 S)-5-methoxy-6-methylflavan-7-ol (XJ-2) was determined to be the best-screened monomer. The effects of XJ-2 on the production of reactive oxygen species (ROS) and Ca2+ in HaCaT cells were investigated using fluorescent probes and flow cytometry, respectively. The impact of XJ-2 on the expression of crucial proteins within the NF-κB pathway was examined via immunofluorescence and western blotting. The expression levels of downstream inflammatory factors, namely IL-1β and TNF-α, were detected through PCR. The effects of XJ-2 on the expression of skin barrier-related factors filaggrin (FLG), aquaporin 3 (AQP-3), and claudin1 (CLDN1) were investigated using PCR, immunofluorescence, and western blotting. Based on these findings, we comprehensively examined the mechanisms underlying the anti-inflammatory and barrier repair effects of XJ-2. XJ-2 primarily protected the internal structure and function of the cells by inhibiting the mass production of ROS and Ca2+ inflow. XJ-2 exerts anti-inflammatory effects by regulating the key proteins of the NF-κB/IKKα pathway and reducing the expression of inflammatory factors. XJ-2 repairs skin barrier damage by regulating multiple factors. Compound XJ-2 from D. draco exerts excellent anti-inflammatory and barrier repair effects, possesses great potential for the treatment of skin diseases, and can be used as a dermatological drug to repair skin barrier damage.